Sensitivity improvement of an electrical sensor achieved by control of biomolecules based on the negative dielectrophoretic force - Kim, Hye Jin; Kim, Jinsik; Yoo, Yong Kyoung; Lee, Jeong Hoon; Park, Jung Ho; Hwang, Kyo Seon (ELSEVIER ADVANCED TECHNOLOGY, 2016)
Effective control of nano-scale biomolecules can enhance the sensitivity and limit of detection of an interdigitated microelectrode (IME) sensor. Manipulation of the biomolecules by dielectrophoresis (DEP), especially the negative DEP (nDEP) force, so that they are trapped between electrodes (sensing regions) was predicted to increase the binding efficiency of the antibody and target molecules, leading to a more effective reaction. To prove this concept, amyloid beta 42 (Af342) and prostate specific antigen (PSA) protein were respectively trapped between the sensing region owing to the nDEP force under 5 V and 0.05 V, which was verified with COMSOL simulation. Using the simulation value, the resistance change (AR/Rb) of the IME sensor from the specific antibody-antigen reaction of the two biomolecules and the change in fluorescence intensity were compared in the reference (pDEP) and nDEP conditions. The AR/Rb value improved by about 2-fold and 1.66-fold with nDEP compared to the reference condition with various protein concentrations, and these increases were confirmed with fluorescence imaging. Overall, nDEP enhanced the detection sensitivity for A beta(42) and PSA by 128% and 258%, respectively, and the limit of detection improved by up to 2-orders of magnitude. These results prove that DEP can improve the biosensor's performance. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: BIOSENSOR